Socialism as a resolution to COVID-19 crises: contribution from the cuban experience - Miglioli, Aline Marcondes (2020)
This article aims to present the objective conditions prior to the COVID-19’s pandemic -that facilitated or limited the capacity of contention of the new disease in Cuba. To this propose, it is presented the Cuban strategy to face the new disease, emphasizing the social isolation as part of the health protocol as an essential step to contain the disease and, therefore, by responsibility and execution of the National Health System. The reflections on how Cuba has faced this new disease, it´s appreciation of human life and it´s solidarity are only possible where prevails the institutions and values of an socialist society, which, therefore, leads us to revalidate socialism as the only possible option for the future of humanity.